Depressive-Like Behavior in Adolescents after Maternal Separation: Sex Differences, Controllability, and GABA - Leussis, Melanie P. (Dev Neurosci, 2012)
Exposure to adversity during development is an identified risk factor for depression later in life. In humans, early adversity accelerates the onset of depressive symptoms, which manifest during adolescence. Animal studies have used maternal separation as a model of early adversity to produce adult depressive-like behaviors, but have yet to examine these behaviors during adolescence. Moreover, the nature of depressive-like behaviors has not been well characterized in this model. Here, we used the triadic model of learned helplessness to understand controllability, helplessness, and motivational factors following maternal separation in male and female adolescent rats. We found sex-dependent changes in the effects of separation, with males demonstrating loss of controllability in an escapable shock condition, whereas females demonstrated motivational impairment in a no-shock condition. The effect, however, did not endure as adult females were no longer helpless. Reductions in parvalbumin, a GABAergic marker, in the prefrontal cortex of separated subjects relative to age-matched controls were evident and paralleled depressive-like behavior. Understanding the risk factors for depression, the nature of depressive-like behaviors, and their unique sex dependency may ultimately provide insight into improved treatments.